Diabetes-Related Lower Extremities Amputations in Saudi Arabia: The Magnitude of the Problem - Alzahrani, Hasan Ali (The Editorial Committee of Annals of Vascular Diseases, 2012)
Background: Data on diabetes-related lower extremities amputations in the Kingdom of Saudi Arabia (KSA) and perhaps in all of Middle East and North African (MENA) countries are limited, in view of the absence of national registries. Methods: This review aims to challenge media figures by review of data in the local database of the author, available published data, as well as by analysis of recent annual reports of the Saudi Ministry of Health to estimate the magnitude of the problem. Different methods of analysis are used based on the number of beds, operations and admissions in KSA to generate approximate figures of the annual expected numbers of amputations in KSA and MENA countries. The 2010 International Diabetes Federation IDF comparative prevalence rate of 16.8% was used to standardize the analysis methods. Results: Findings of 2 previous studies and 3 analytical methods led me to the prediction that about 325 amputations are likely to occur annually in Jeddah compared to 741 in Riyadh and 3970 in KSA. When we applied the results of KSA to those of MENA countries, 44208 amputations were predicted annually. Conclusion: Half a million diabetes-related amputations of the lower extremities are likely to occur in KSA and MENA countries over the coming decade. National registries are urgently needed.